Reactivity of Cetophenone and Its Derivatives with Semi-Empirise Methods Parameterizedmodel 6 (PM6) - Topan Setiawan; Saras Wati Banapon; Intan Sapsuha; Wahyu Yusup Duwila (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
Cetophenone is used as an intermediate in the synthesis of flavones. In industry, Cetophenone is obtained as a by-product of the oxidation of ethyl benzene. The method used for modeling Cetophenone derivatives is a semi-empirical method using (PM6). The cetophenone derivative which has a larger energy difference is found in the compound 2-aceyiylisophyhaloitrile. The highest value of electronegativity and chemical hardness was found in the compound 2-aceyiylisophyhaloitrile and the greatest potential energy value was found in the compound 2-aceyiylisophyhaloitrile.